Calidad bacteriológica del agua para consumo humano en zonas de alta marginación de Chiapas Bacteriological quality of drinking water in areas of high levels of poverty in Chiapas, Mexico - Héctor Javier Sánchez-Pérez; María Guadalupe Vargas-Morales; José Domingo Méndez-Sánchez (Instituto Nacional de Salud Pública, 2000)
OBJETIVO: Analizar la calidad bacteriológica del agua (CBA) para consumo humano y su relación con diarreas y enteroparasitosis en niños de 1 a 14 años en comunidades de alta marginación socioeconómica de Chiapas, México. MATERIAL Y MÉTODOS: En una muestra aleatoria de 99 viviendas de la Región Fronteriza de Chiapas, de marzo a septiembre de 1998, se recolectaron muestras de agua para consumo humano, se indagó sobre diarreas en los últimos 15 días y se recolectaron muestras de heces de 322 niños de 1 a 14 años. La CBA se determinó mediante la técnica de filtración por membranas y las enteroparasitosis por el método de Faust. Se utilizó el estadístico ji² para el análisis de la CBA con relación a los diversos factores analizados. RESULTADOS: Sólo 31% de las muestras de agua fueron aptas para consumo humano. La CBA y la presencia de diarreas referida por las madres de los menores no mostraron asociación. Los niños con mala CBA en sus viviendas mostraron mayor prevalencia de Entamoeba histolytica y mayor tendencia a estar parasitados. CONCLUSIONES: Es necesario desarrollar medidas que mejoren la CBA y campañas de educación que incrementen el uso de agua hervida, su manejo adecuado y el cuidado de las fuentes de abastecimiento comunitarias. OBJECTIVE: To analyze the bacteriological quality of drinking water (BQDW) and its association with diarrhoea and intestinal parasites in children 1 to 14 years old, in areas of high levels of poverty in Chiapas, Mexico. MATERIAL AND METHODS: From March to September 1998, drinking water was collected from a random sample of 99 households in the Border Region of Chiapas, Mexico; data on diarrhoeal disease (in the past 15 days) were collected and stool testing for intestinal parasites was performed in children 1 to 14 years old (n= 322). The BQDW was determined by the filtration membrane technique. Intestinal parasitic infections were determined by the Faust Method. The chi² statistic was used to analyse factors associated with BQDW. RESULTS: Only 31% of the water samples were adequate for human consumption. The BQDW and the presence of diarrhoea (informed by the mothers of the children) showed no association. Children living in households with inadequate BQDW had a higher prevalence of Entamoeba histolytica and a greater tendency to have intestinal parasites. CONCLUSIONS: It is necessary to develop programs that improve BQDW and to develop education efforts aimed at increasing the use of boiled water and the adequate management and care of community water storage sites.